Kenyamanan Penggunaan Alat Pelindung Diri Relawan COVID-19 di Kota Binjai - Rifqi Fadilla Neraz; Tri Niswati Utami (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The number of COVID-19 cases is increasing every day, so volunteers are needed to help the government deal with the outbreak. Volunteers are at risk of being exposed to COVID-19, one way to protect themselves from transmission is to use Personal Protective Equipment (PPE). However, volunteers complain that they are not comfortable using PPE and work. The research objective was to analyze the comfort of using the personal protective equipment for COVID-19 volunteers in Binjai City. Cross-sectional study design. The sampling technique in this study was total sampling. Data analysis using multiple logistic regression test. The results showed that sensory movements significantly affected the comfort of personal protective equipment with a p-value of 0.000 and Exp (B) 28.153. Flexibility affects the comfort of personal protective equipment significantly as evidenced by the p-value of 0.000 and Exp (B) 20,909. The dominant factor affecting the comfort of personal protective equipment is the variable sensory movement. Personal protective equipment that interfered with sensory movements had 28 times the effect of discomfort for volunteers than those that did not interfere with sensory movements. It is hoped that the person in charge of the Covid-19 task force unit to choose good personal protective equipment so as to provide comfort to volunteers. Keywords: COVID-19; personal protective equipment; comfort; volunteer ABSTRAK Kasus COVID-19 meningkat setiap hari jumlahnya, sehingga dibutuhkan relawan untuk membantu pemerintah menangani wabah tersebut. Relawan berisiko perpapar COVID-19, salah satu cara melindungi diri dari penularan adalah menggunakan Alat Pelindung Diri (APD). Namun relawan mengeluh tidak nyaman menggunakan APD dan pekerjaan. Tujuan penelitian menganalisis kenyamanan penggunaan alat pelindung diri relawan COVID-19 di Kota Binjai. Desain penelitian cross-sectional. Teknik pengambilan sampel dalam penelitian ini adalah total sampling. Analisis data dengan uji regresi logistic berganda. Hasil penelitian menunjukkan gerakan sensori memengaruhi kenyamanan alat pelindung diri secara signifikan nilai dibuktikan dengan p-value 0,000 dan Exp (B) 28,153. Fleksibilitas memengaruhi kenyamanan alat pelindung diri secara signifikan dibuktikan dengan p-value 0,000 dan Exp (B) 20,909. Faktor dominan memengaruhi kenyamanan alat pelindung diri adalah variabel gerakan sensori. Alat pelindung diri yang mengganggu gerakan sensori memberikan pengaruh 28 kali rasa tidak nyaman bagi relawan dibandingkan yang tidak mengganggu gerakan sensori. Diharapkan penanggung jawab satuan gugus tugas covid-19 untuk memilih alat pelindung diri yang ensi yang baik sehingga memberikan kenyamanan pada relawan. Kata kunci: COVID-19; alat pelindung diri; kenyamanan; relawan